(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, we investigate the concept of happiness from etymological and explanatory dictionaries, as well as Russian poetry, to gain a deeper understanding of its various dimensions and sources. Happiness is consistently compared to light and fire, illustrating its ephemeral and illuminating qualities. Our analysis reveals that happiness can be defined as a positive emotional state arising from a favorable evaluation of one’s own destiny. Perspectives on happiness can be classified according to the source, such as external goods, pleasant feelings, cherished work, family, and altruistic interests, which act as factors contributing to happiness. We conclude that happiness is primarily a mental state, heavily influenced by an individual’s life attitudes and expectations. This insight into the concept of happiness can serve as a foundation for further exploration of its psychological and sociocultural implications, as well as the development of strategies to promote happiness and well-being in various contexts.